2020
DOI: 10.3390/cancers12020421
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-Fucoidan Prevents M2 Macrophage Differentiation and HCT116 Tumor Progression

Abstract: Reactive oxygen species (ROS) produced during intracellular metabolism or triggered by extrinsic factors can promote neoplastic transformation and malignant microenvironment that mediate tumor development. Oligo-Fucoidan is a sulfated polysaccharide isolated from the brown seaweed. Using human THP-1 monocytes and murine Raw264.7 macrophages as well as human HCT116 colorectal cancer cells, primary C6P2-L1 colorectal cancer cells and human MDA-MB231 breast cancer cells, we investigated the effect of Oligo-Fucoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Similarly, there was a report that extract from the seaweed Cladosiphon novae-caledoniae consisting of a digested small molecular weight fraction (72%; <500 Da) and a non-digested fraction (less than 28%; peak = 800 kDa) enhanced the anti-cancer effects of CDDP via inhibitory effects on cell growth (using 200 and 400 μg/mL fucoidan extract for 48 h) and the pro-apoptotic activity (using 200 μg/mL fucoidan extract for 24 and 48 h) in breast cancer cells (MDA-MB-231 and MCF-7 cells) [ 64 ]. Furthermore, in recent years, oligo-fucoidan (molecular weight: 92.1%; 500–800 Da) has been reported to promote the cytotoxic activity of CDDP in colon cancer cells [ 12 ]. Briefly, in primary C6P2-L1 cell lines derived from colorectal cancer patients, the number of apoptotic cells in the group treated with a combination of CDDP and oligo-fucoidan was significantly higher than those in groups treated with CDDP alone or oligo-fucoidan alone, and upregulation of PARP cleavage and caspase-3 activation were associated with these results [ 12 ].…”
Section: Combination Of Fucoidan and Conventional Chemotherapeuticmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, there was a report that extract from the seaweed Cladosiphon novae-caledoniae consisting of a digested small molecular weight fraction (72%; <500 Da) and a non-digested fraction (less than 28%; peak = 800 kDa) enhanced the anti-cancer effects of CDDP via inhibitory effects on cell growth (using 200 and 400 μg/mL fucoidan extract for 48 h) and the pro-apoptotic activity (using 200 μg/mL fucoidan extract for 24 and 48 h) in breast cancer cells (MDA-MB-231 and MCF-7 cells) [ 64 ]. Furthermore, in recent years, oligo-fucoidan (molecular weight: 92.1%; 500–800 Da) has been reported to promote the cytotoxic activity of CDDP in colon cancer cells [ 12 ]. Briefly, in primary C6P2-L1 cell lines derived from colorectal cancer patients, the number of apoptotic cells in the group treated with a combination of CDDP and oligo-fucoidan was significantly higher than those in groups treated with CDDP alone or oligo-fucoidan alone, and upregulation of PARP cleavage and caspase-3 activation were associated with these results [ 12 ].…”
Section: Combination Of Fucoidan and Conventional Chemotherapeuticmentioning
confidence: 99%
“…Furthermore, in recent years, oligo-fucoidan (molecular weight: 92.1%; 500–800 Da) has been reported to promote the cytotoxic activity of CDDP in colon cancer cells [ 12 ]. Briefly, in primary C6P2-L1 cell lines derived from colorectal cancer patients, the number of apoptotic cells in the group treated with a combination of CDDP and oligo-fucoidan was significantly higher than those in groups treated with CDDP alone or oligo-fucoidan alone, and upregulation of PARP cleavage and caspase-3 activation were associated with these results [ 12 ]. This study also showed that oligo-fucoidan enhanced the anti-tumor effects of CDDP in colorectal cancer cells in vivo.…”
Section: Combination Of Fucoidan and Conventional Chemotherapeuticmentioning
confidence: 99%
See 3 more Smart Citations